2002
DOI: 10.1021/jp021275z
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Simple Hydrocarbons on Platinum Cluster Ions

Abstract: Reactions of size-selected platinum cluster ions, Pt n + (n ) 1-5), with small hydrocarbon molecules (CH 4 , C 2 H 6 , C 2 H 4 , and C 2 H 2 ) were studied in a beam-gas cell geometry at collision energies less than 1 eV employing a tandem mass spectrometer. It was found that dehydrogenation of the hydrocarbon molecules proceeds exclusively on Pt n + and the absolute cross sections of the reactions depend critically on the cluster size, n, and the collision energy. The size-and the collision energy-dependent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…Our calculated results are in good agreement with the experimental observations of Uggerud et al [20,21]. As seen in Figure 1b and c, following both mechanisms, the PESs for the second reductive dihydrogen-elimination (the rear half of PESs of twofold dehydrogenation) are uphill in energy, and various reaction pathways in the whole reaction of the second reductive dihydrogen-elimination are strongly endothermic by 30.7-53.2 kcal/mol with much higher barriers for the rate-determining steps.…”
Section: Twofold Dihydrogen Elimination Of Ethanesupporting
confidence: 92%
See 1 more Smart Citation
“…Our calculated results are in good agreement with the experimental observations of Uggerud et al [20,21]. As seen in Figure 1b and c, following both mechanisms, the PESs for the second reductive dihydrogen-elimination (the rear half of PESs of twofold dehydrogenation) are uphill in energy, and various reaction pathways in the whole reaction of the second reductive dihydrogen-elimination are strongly endothermic by 30.7-53.2 kcal/mol with much higher barriers for the rate-determining steps.…”
Section: Twofold Dihydrogen Elimination Of Ethanesupporting
confidence: 92%
“…The experimental observation by Allison et al showed that the transition-metal ions can activate C-C and C-H bonds of alkanes [19]. In particular, the reaction of platinum ion with ethane was previously studied in a beam-gas cell geometry at collision energies less than 1 eV employing a tandem mass spectrometer [20], and dehydrogenation of the hydrocarbon was found to be the main process. Uggerud et al later measured the reactivity of Pt + with ethane under single-collision conditions in a Fourier-transform ion cyclotron resonance mass spectrometer [21].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of platinum in catalysis has lead to gasphase platinum clusters being the subject of a number of experiments to probe their reactivity, [12][13][14][15][16][17][18][19] which has been found to depend sensitively on cluster size and charge state. Little spectroscopic work has been undertaken on unsupported platinum clusters, though features consistent with two vibrational progressions, at 105 ± 30 and 225 ± 30 cm −1 , have been observed in the photoelectron spectrum of Pt …”
mentioning
confidence: 99%
“…Platinum is one of the most important metal catalysts with applications including hydrogenation, dehydrogenation, and cracking of various hydrocarbons. Considering the importance of these processes, it comes as no surprise that many of the corresponding reactions have been studied using platinum clusters as model systems 16–22. Prior analyses of platinum cluster reactions with benzene have mainly concentrated on neutral and cationic clusters.…”
mentioning
confidence: 99%